My brother, ant - Byars, Betsy (London : PuffinBooks, 1996)
In four separate stories, Ant's older brother gets rid of the monster under Ant's bed, forgives Ant for drawing on his homework, tries to read a story, and helps Ant write a letter to Santa.
Keywords: Brothers - Fiction